2019
DOI: 10.1002/bjs.11064
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of percutaneous biopsy in retroperitoneal sarcoma

Abstract: Background: Percutaneous biopsy is recommended before surgery for suspected retroperitoneal sarcoma (RPS) to confirm the histological diagnosis and guide surgical strategy. The present study aimed to establish the diagnostic accuracy of percutaneous core biopsy with respect to histological diagnosis and tumour grade. Methods: Data on patients with suspected RPS who underwent percutaneous biopsy followed by surgical resection between 2005 and 2016 at one of two tertiary European sarcoma units were reviewed. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
(17 reference statements)
0
22
0
6
Order By: Relevance
“…Percutaneous biopsy is recommended prior to surgery for suspected RPS; it can also guide the surgical approach and follow-up protocol 18 . According to the ESMO recommendations, following an appropriate imaging evaluation, the standard approach to RPS diagnosis includes multiple core-needle biopsies using ≥14–16 G needles.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous biopsy is recommended prior to surgery for suspected RPS; it can also guide the surgical approach and follow-up protocol 18 . According to the ESMO recommendations, following an appropriate imaging evaluation, the standard approach to RPS diagnosis includes multiple core-needle biopsies using ≥14–16 G needles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the difficulty in the diagnosis of dedifferentiated liposarcoma (DDLPS) in preoperative biopsy. 7 In our series, the rate of NLR high among well-differentiated liposarcoma (WDLPS) was 63.9% and 72% in DDLPS (P = .48). Interestingly, IL-6 a marker of innate immune response was associated in that study with tumor grade.…”
Section: Comparison Of Diagnostic Accuracy Of Preoperative Biopsy Amentioning
confidence: 55%
“…If this finding is verified in other studies, than NLR may complement or substitute the data gained by preoperative biopsy. However, others 7 have reported higher sensitivity of preoperative biopsy for high-grade tumors, which may perform better than NLR. Although NLR failed to discriminate between WDLPS and DDLPS in our series, it is possible that elevated NLR may point to an aggressive biology even in WDLPS histology, a hypothesis that needs to be checked in larger cohorts.…”
mentioning
confidence: 91%
“…The concordance rate of needle biopsy for benign tumors is reported to be low; the sensitivity was 77%, specificity was 96%, positive predictive value was 77% and negative predictive value was 96%. 32 According to this study, eight of 35 benign tumors were diagnosed as malignant as follows: two cases were dedifferentiated liposarcomas, four cases were sarcomas of unknown histology and two cases were not sarcomas. Conversely, seven malignant tumors were diagnosed as benign tumors: one case was well-differentiated liposarcoma, one case was leiomyosarcoma, two cases were other sarcomas, one case was a malignant tumor excluding RPS and two cases were unknown diagnoses.…”
Section: Validation Of Needle Biopsymentioning
confidence: 86%
“…63 Over recent years, the CT-guided biopsy approach through the retroperitoneum was found to have a higher value than ultrasound-guided biopsy. 32 Some guidelines recommend the collection of four to six cores using needle Table 1 Retroperitoneal sarcomas by sex, age, tumor size and histology from previous reports Huggett et al 50 van Dalen et al 52 Nathan et al 53 Toulmonde et al 54 Gronchi et al 55 Raut et al 56 Gronchi et al 57 Garcia-Ortega et al 58 No biopsy with a thickness of ≥16-G and a method without aspiration cytology. [34][35][36] The risk of tumor dissemination by needle biopsy is lower with the posterior approach than the transperitoneal approach.…”
Section: Diagnosis Of Rpssmentioning
confidence: 99%